Ultrasound findings of ovarian intravenous leiomyomatosis: a case report - Li, Jin; Luo, Le (Frontiers in Oncology, 2024)
Intravenous leiomyomatosis (IVL), an abnormal growth pattern of uterine leiomyomas, is a rare tumor characterized by masses of smooth muscle cells appearing histologically benign and proliferating within the blood vessels but not invading the tissue. Currently, there have been limited reports of early cases of IVL, and the imaging characteristics of IVL remain uncertain, resulting in frequent misdiagnosis prior to surgery. The present study utilized a case of early IVL detected through conventional ultrasound and subsequently confirmed via contrast-enhanced ultrasound (CEUS) to further investigate ultrasound’s diagnostic efficacy for early IVL detection. Here, a case of a 49-year-old woman was reported who presented with uterine leiomyoma and an echogenic mass in the left adnexal region on physical examination. Subsequent transvaginal CEUS examination revealed a left ovarian venous leiomyoma. The patient underwent resection of tumors in the uterus, bilateral ovaries, and left ovarian vein under general anesthesia. A venous plexus was identified above the left broad ligament close to the left ovary, and a myoma-like growth was detected in the posterior uterine wall during the operational procedure. Reports on pathology and immunohistochemistry verified leiomyomatosis with fatty metaplasia in the left broad ligament and uterine wall vein. The prognosis of patients with IVL is determined based on the appropriate surgical methods and the timely diagnosis of the condition. In this case, conventional ultrasound aided in the early identification of IVL, which was later verified by a CEUS examination, resulting in a successful surgical treatment. This example highlights the importance of ultrasound technology in diagnosing this uncommon condition and presents a new method for preoperative detection of IVL.